Stanley Kubrick : Interviews. - Phillips, Gene D. (University Press of Mississippi, 2013)
From his first feature film, Fear and Desire (1953), to his final, posthumously released Eyes Wide Shut (1999), Stanley Kubrick excelled at probing the dark corners of human consciousness. In doing so, he adapted such popular novels as The Killing, Lolita, A Clockwork Orange, and The Shining and selected a wide variety of genres for his films -- black comedy (Dr. Strangelove), science fiction (2001: A Space Odyssey), and war (Paths of Glory and Full Metal Jacket). Because he was peerless in unveiling the intimate mysterie.